Aulton's pharmaceutics : the design and manufacture of medicines - Aulton, Michael E.; Taylor, Kevin, 1961- (Edinburgh ; New York : Elsevier, 2018)
A comprehensive textbook covering the design of dosage forms and all aspects of drug delivery systems. Pharmaceutics in its broadest sense is the 'art of the apothecary' or, in simple terms, pharmaceutical preparations. It remains a diverse subject in the pharmacy curriculum, encompassing design of drugs, their manufacture and the elimination of micro-organisms from the products. This books encompasses all of those areas.
What is pharmaceutics? --
Design of dosage forms --
Scientific principles of dosage form design --
Particle science and powder technology --
Pharmaceutical microbiology and serialization --
Biopharmaceutical principles of drug delivery --
Dosage form design and manufacture --
Packaging and stability of pharmaceutical products.
PHR
HYE Trade International
Keywords: Drugs -- Design; Drugs -- Dosage forms; Biopharmaceutics; Pharmaceutical technology; Pharmaceutical chemistry; Pharmacy